Proximate, total phenolic and total flavonoid content of oxalis barrelieri juice - Chao, Teh Yu (Universiti Sains Malaysia, 2013)
Oxalis barrelieri is a common weed found in Malaysia which has been used as medical herbs by the local traditional medicinal practitioners for generation. Recently Oxalis barrelieri has been discovered to have the ability to treat diabetes mellitus and it has potential to become herbal remedy for diabetes mellitus. With the surging development in functional food and herbal products, Oxalis barrelieri had been made into herbal beverages for reducing the risk of getting diabetes mellitus II. The objective of this study was to determine the proximate analysis, total phenolic content (TPC) and total flavonoid content (TFC), and determine the suitable concentration of Oxalis barrelieri to develop as functional herbal juice. Three different concentration of OB herbal juice (10%, 15%, and 20%) were analyzed using proximate test, TPC and TFC for nutritional composition. The proximate were determined by AOAC Official Methods. TPC was determined using Folin-Ciocalteu assay while TFC was determined using aluminum chloride colorimetric assay. OB juice showed significant highest of moisture in 10% concentration (87.73%). Ash showed highest in 20% concentration (0.32%). Carbohydrate and crude fiber showed significant highest in 20% concentration (21.57% and 3.19% respectively). TPC and TFC showed significant increases in all concentration (range of TPC: 16.22-29.74 mg GAE/g; TFC: 38.12-59.10 mg CE/g) compared to control. Thus, as conclusion, Oxalis barrelieri in 20% concentration show potential as functional beverages.